Periconceptional and prenatal exposure to metal mixtures in relation to behavioral development at 3 years of age. Issue 4 (6th August 2020) - Doherty, Brett T.; Romano, Megan E.; Gui, Jiang; Punshon, Tracy; Jackson, Brian P.; Karagas, Margaret R.; Korrick, Susan A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Behavioral effects of prenatal exposure to mixtures of essential and toxic metals are incompletely understood. Methods: We investigated neurodevelopmental effects of prenatal metal exposures in the New Hampshire Birth Cohort Study, a prospective birth cohort. We measured metals (As, Cu, Mn, Pb, Se, Zn) in maternal prenatal and postnatal toenails and infant toenails, reflecting exposures during periconception and early pregnancy, mid pregnancy, and late pregnancy and early neonatal life, respectively. Mothers completed the Social Responsiveness Scale, 2nd ed. (SRS-2) and the Behavior Assessment System for Children, 2nd ed. (BASC-2) to assess their child's neurobehavior at 3 years. We used mean field variational Bayes for lagged kernel machine regression to investigate associations of toenail metal concentrations with SRS-2 Total Scores and BASC-2 composite scores (SRS-2: n = 371; BASC-2: n = 318). Results: Infant toenail Mn was associated with poorer performance on multiple BASC-2 composite scores. Maternal postnatal toenail As was associated with worse scores on the BASC-2 Internalizing Problems and Behavioral Symptoms Index. Associations with Mn were generally stronger in males, and associations with As were generally stronger in females. Other metals, including Pb, were weakly or inconsistently associated with BASC-2 outcomes, and there were no strong associations of individual metals and SRS-2 Total Scores. We observed suggestive evidence of interaction between As and Se for SRS-2 Total Scores and BASC-2 Adaptive Skills, though overall evidence of interactions between metals was weak. Conclusion: Our results support the hypothesis that exposure to Mn and As in mid to late pregnancy may be neurodevelopmentally harmful.